Periodontal ligament and root pulp in the estimation of chronological age in Peruvian population - Carhuamaca-León, Denisse (2020)
Objective. Determine the effectiveness between radiographic methods of the periodontal ligament and root pulp of the lower third molars, in the estimation of chronological age. Methods. Through a cross-sectional design, using a sample of 347 digital panoramic radiographic images (187 males, 160 females) between 16 and 74 years old. The estimation of chronological age was based on the classification of stages proposed by Olze, with a intra-examiner and inter-examiner agreement was determined by Cohen's Kappa Test. The relationship among the chronological age, the stages of the periodontal ligament and the root pulp were assessed using Spearman and Pearson rank-order correlation. The Wilcoxon test estimated the difference between dental pieces 38-48, with a level of significance p<0.05. Results. There was a medium and long positive correlation. There was a significant difference between the lower third molars in both methods. Also, there wasn´t a significant difference between age chronology and age estimation with the study of root pulp of dental and with the study of periodontal ligament. Conclusions. The radiographic method of the root pulp in the right lower third molar is more precise than the periodontal ligament. Likewise, the radiographic study method of the periodontal ligament of the left lower third molar is more efficient than of the root pulp.